Tablet Disintegration and Dispersion under In Vivo-like Hydrodynamic Conditions - Jan Lenz; Frederik Fuest; Jan Henrik Finke; Heike Bunjes; Arno Kwade; Michael Juhnke (MDPI AG, 2022)
Disintegration and dispersion are functional properties of tablets relevant for the desired API release. The standard disintegration test (SDT) described in different pharmacopoeias provides only limited information on these complex processes. It is considered not to be comparable to the biorelevant conditions due to the frequent occurrence of high hydrodynamic forces, among other reasons. In this study, 3D tomographic laser-induced fluorescence imaging (3D Tomo-LIF) is applied to analyse tablet disintegration and dispersion. Disintegration time (DT) and time-resolved particle size distribution in close proximity to the tablet are determined in a continuously operated flow channel, adjustable to very low fluid velocities. A case study on tablets of different porosity, which are composed of pharmaceutical polymers labelled with a fluorescent dye, a filler, and disintegrants, is presented to demonstrate the functionality and precision of the novel method. DT results from 3D Tomo-LIF are compared with results from the SDT, confirming the analytical limitations of the pharmacopoeial disintegration test. Results from the 3D Tomo-LIF method proved a strong impact of fluid velocity on disintegration and dispersion. Generally, shorter DTs were determined when cross-linked sodium carboxymethly cellulose (NaCMCXL) was used as disintegrant compared to polyvinyl polypyrrolidone (PVPP). Tablets containing Kollidon VA64 were found to disintegrate by surface erosion. The novel method provides an in-depth understanding of the functional behaviour of the tablet material, composition and structural properties under in vivo-like hydrodynamic forces regarding disintegration and the temporal progress of dispersion. We consider the 3D Tomo-LIF in vitro method to be of improved biorelevance in terms of hydrodynamic conditions in the human stomach.